Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/19401493.2020.1813198
|View full text |Cite
|
Sign up to set email alerts
|

A study on the integration of air-source heat pumps, solar collectors, and PCM tanks for outdoor swimming pools for winter application in subtropical climates

Abstract: This study presents a new integration of air-source heat pumps, solar collectors and PCM tank regarding the dynamics of outdoor swimming pools, and investigates its application in outdoor swimming pools for extending their availability in winter season for subtropical climates. The proposed integration system harvests heat from both ambient air via air-source heat pumps and solar radiation via solar collectors. PCM tank are introduced to shift the electricity use from the on-peak to off-peak period in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…u,HCOP=(((∂HCOP/∂Q,gcr)×u,Q,gcr) 2 +((∂HCOP/∂P, cmr)×u,P,cmr) 2 ) 0.5 (6) where u,Q,gcr is the uncertainty of the ,̇, and u,P,cmr is the uncertainty of the P,cmr. The u,Q,gcr was calculated as: u,Q,gcr=(((∂Q,gcr/∂m,gcr)×u,m,gcr) 2 +((∂Q,gcr/∂T,gc r,o)×u,T,gcr,o) 2 +((∂Q,gcr/∂T,gcr,i)×u,T,gcr,i) 2 ) 0.5 (7) where u,m,gcr is the uncertainty of the m,gcr, u,T,gcr,o is the uncertainty of the T,gcr,o, and u,T,gcr,i is the uncertainty of the T,gcr,i.…”
Section: Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…u,HCOP=(((∂HCOP/∂Q,gcr)×u,Q,gcr) 2 +((∂HCOP/∂P, cmr)×u,P,cmr) 2 ) 0.5 (6) where u,Q,gcr is the uncertainty of the ,̇, and u,P,cmr is the uncertainty of the P,cmr. The u,Q,gcr was calculated as: u,Q,gcr=(((∂Q,gcr/∂m,gcr)×u,m,gcr) 2 +((∂Q,gcr/∂T,gc r,o)×u,T,gcr,o) 2 +((∂Q,gcr/∂T,gcr,i)×u,T,gcr,i) 2 ) 0.5 (7) where u,m,gcr is the uncertainty of the m,gcr, u,T,gcr,o is the uncertainty of the T,gcr,o, and u,T,gcr,i is the uncertainty of the T,gcr,i.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Yu et al [6] concluded that the heat pump systems were suitable for spacing heating purpose, because their energy-saving potential is considerable. Li et al [7] presented an investigation of an outdoor swimming pool heating system for winter application. The air-source heat pump, solar collectors, and PCM storage tank were integrated in the investigated system.…”
Section: Introductionmentioning
confidence: 99%